Designing The Arabic Learning Book Based on The Hiwar Approach for Non-Arabic Education Program at Muhammadiyah Islamic University of Sinjai (ar) - Husnaini Jamil; Nur Agung (AL-TA'RIB : Jurnal Ilmiah Program Studi Pendidikan Bahasa Arab IAIN Palangka Raya, 2019)
Learning Arabic has become the inseparable part of the curriculum of Islamic universities in Indonesia. Its presence is expected to improve the students